Integration of Mahalanobis-Taguchi System and activity based costing for remanufacturing decision - Nik Nurharyantie, Nik Mohd Kamil; Mohd Yazid, Abu (Universiti Malaysia Pahang, 2018)
Remanufacturing is a process that returns the second hand and used product that have the performance similar or better than the new product. The remanufacturer cannot be predicting the end of life (EOL) of crankshaft to remanufacture, repair or reject due to the limited information provided by Original Equipment Manufacturer (OEM) which depend on a traditional inspection to make a decision. Subsequently, Traditional Cost Accounting (TCA) which the manufacturing overhead are driven by the production volume are being applied. The aim of this work is to develop a distinctive pattern of crankshaft and identify the critical and non-critical parameter of crankshaft based on the Mahalanobis Taguchi System (MTS), then applied the Activity Based Costing (ABC) as a method of estimation for the remanufacturing cost of crankshaft. In methodology, the scatter diagram is construct to develop the pattern recognition using T Method-3, Taguchi orthogonal array (OA) are applied to identify the important parameter using T Method and lastly, the ABC system is analysed the costing of critical parameters. Quality inspection is the most important in quality inspection to reduce the number of parameter of each engine model and to compare which costing system can produce the cheapest price. Therefore, it is also to prove the combination of applying MTS method with ABC system will make the profitability and manufacturing cost are more accurate.